2019
DOI: 10.1371/journal.pmed.1002825
|View full text |Cite
|
Sign up to set email alerts
|

Changes in resistance among coliform bacteraemia associated with a primary care antimicrobial stewardship intervention: A population-based interrupted time series study

Abstract: Background Primary care antimicrobial stewardship interventions can improve antimicrobial prescribing, but there is less evidence that they reduce rates of resistant infection. This study examined changes in broad-spectrum antimicrobial prescribing in the community and resistance in people admitted to hospital with community-associated coliform bacteraemia associated with a primary care stewardship intervention. Methods and findings Segmented regression analysis of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Reducing antibiotic resistance is a national and international priority, and the UK aims to reduce antibiotic use in humans in the community by 25% by 2024, from the 2013 baseline [ 1 ]. National levels of antibiotic resistance correlate with rates of antibiotic prescriptions [ 2 ] and reducing primary care consumption is associated with reduced resistance [ 3 ]. At an individual level, risk of antibiotic-resistant infection is over twice as high if an antibiotic has been taken in the past year [ 4 ] and this increases the risk of clinical treatment failure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing antibiotic resistance is a national and international priority, and the UK aims to reduce antibiotic use in humans in the community by 25% by 2024, from the 2013 baseline [ 1 ]. National levels of antibiotic resistance correlate with rates of antibiotic prescriptions [ 2 ] and reducing primary care consumption is associated with reduced resistance [ 3 ]. At an individual level, risk of antibiotic-resistant infection is over twice as high if an antibiotic has been taken in the past year [ 4 ] and this increases the risk of clinical treatment failure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Antimicrobial stewardship program implementation in primary care settings can reduce broad-spectrum antimicrobial use. 14 As studies keep identifying potentially inappropriate antimicrobials prescribed with duration of treatment outside of guideline-based range, 15 more collaboration among physicians and community pharmacists and greater involvement of community pharmacists in antimicrobial stewardship programs should be encouraged. This study included community pharmacists, family medicine other physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Three other studies on the association between antibiotic use and AMR in primary care show conflicting results [ 7 , 8 , 13 ]. In line with our findings, Butler et al showed a statistically significant reduction in ampicillin and trimethoprim resistance per 1000 registered patients for practices that significantly reduced antibiotic dispensing over several years [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…No data on numbers of tests, or resistance percentages with numbers of cultures as denominators were given. Hernandez-Santiago et al found less community-associated resistant coliform bacteraemia among adult patients as a result of antibiotic stewardship interventions [ 8 ]. Hay et al used individual patient data to investigate the relationship between prescribed antibiotics and the development of AMR using urine isolates of asymptomatic adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation